2019
DOI: 10.1590/1809-2950/18006726032019
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of mobility tests for screening the risk of falls in patients with mild cognitive impairment and alzheimer’s disease

Abstract: Identifying gait and balance disorders in the earlier stages of Alzheimer’s disease (AD) and Mild Cognitive Impairment (MCI) could reduce or prevent falls in older adults. This cross-sectional study aimed to determine which mobility tests best discriminate the risk of falls in MCI and mild AD. Functional mobility was assessed by the timed up and go test (TUG) and 10-meter walk test (10MWT). A calendar of falls was produced, with follow-up via telephone calls during 6 months. For the MCI Group (n=38), time spen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Older adults with AD have a high fall risk, which can be reliably screened using TUGT (Allali & Verghese, 2020;Allali, et al, 2017;Ansai, Andrade & Rossi, et al, 2017;Borges, et al, 2015;Cruz, et al, 2015;Dyer, et al, 2020;Kato-Narita & Radanovic, 2009). We found a higher time to complete the test than previous studies (Alexandre, et al, 2012;Ansai, et al, 2019). Alexandre et al (2012) and Ansai et al (2019) presented a TUGT cutoff point of 12.47 and 17.56 seconds, respectively, for Brazilian older adults with AD.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Older adults with AD have a high fall risk, which can be reliably screened using TUGT (Allali & Verghese, 2020;Allali, et al, 2017;Ansai, Andrade & Rossi, et al, 2017;Borges, et al, 2015;Cruz, et al, 2015;Dyer, et al, 2020;Kato-Narita & Radanovic, 2009). We found a higher time to complete the test than previous studies (Alexandre, et al, 2012;Ansai, et al, 2019). Alexandre et al (2012) and Ansai et al (2019) presented a TUGT cutoff point of 12.47 and 17.56 seconds, respectively, for Brazilian older adults with AD.…”
Section: Discussionmentioning
confidence: 44%
“…Alexandre et al (2012) and Ansai et al (2019) presented a TUGT cutoff point of 12.47 and 17.56 seconds, respectively, for Brazilian older adults with AD. Patients with CDR2 completed the TUGT with median times above these cutoff points (Ansai, et al, 2019;Bortoli, et al, 2015;Podsiadlo & Richardson, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Gait speed was the most investigated falls risk factor with all studies reporting a statistically significant association between falls and slow gait speed in people with Mild Cognitive Impairment. 26,27,37,39,48,52 Dual-task gait performance 24,25,41 and non-amnesic Mild Cognitive Impairment 48,64 were also found to be significantly associated with falls in people with Mild Cognitive Impairment living in the community.…”
Section: Resultsmentioning
confidence: 94%
“…previous 12-months) 28 and only once for the other four studies that all reported the same number of falls in the 6-month prospective data collection period. [24][25][26][27] The same occurred for two other studies, 29,30 where the first published study was the only falls prevalence data utilized in the analysis. 30 For another two studies that used the same participant cohort, 31,32 No single included study answered all three research questions.…”
Section: Study Selection/description Of Studiesmentioning
confidence: 83%
See 1 more Smart Citation